2019
DOI: 10.1186/s12906-019-2698-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytoprotective effects of Pyrola decorata H. Andres and its five phenolic components

Abstract: BackgroundPyrola decorata H. Andres, is exclusively distributed in China and a source of traditional Chinese herbal medicine Luxiancao for more than 2000 years. Here, we evaluated the antioxidant and cytoprotective effects of P. decorata and its five phenolic components (protocatechuic acid, gallic acid, hyperoside, 2′′-O-galloylhyperin, and quercetin), and discussed their antioxidant chemistry.MethodsA lyophilized aqueous extract of P. decorata (LAEP) was prepared and analyzed with high-performance liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…PhUGT was able to galactosylate quercetin (1, Figure S5), myricetin (9, Figure S16), kaempferol (10, Figure S17), taxifolin (11, Figure S18), and aromadendrin (12, Figure 7) to form the corresponding 3-O-galactosides. Conversely, PhUGT displayed no reactivity to flavonoids without 3-OH, such as eriodictyol (13), naringenin (14), luteolin (15), and apigenin (16). These evidences indicated that PhUGT was also an acceptor promiscuous F3GT, recognizing both dihydroflavonols and flavonols instead of only flavonols as reported previously.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…PhUGT was able to galactosylate quercetin (1, Figure S5), myricetin (9, Figure S16), kaempferol (10, Figure S17), taxifolin (11, Figure S18), and aromadendrin (12, Figure 7) to form the corresponding 3-O-galactosides. Conversely, PhUGT displayed no reactivity to flavonoids without 3-OH, such as eriodictyol (13), naringenin (14), luteolin (15), and apigenin (16). These evidences indicated that PhUGT was also an acceptor promiscuous F3GT, recognizing both dihydroflavonols and flavonols instead of only flavonols as reported previously.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…The activities of piceatannol and astringin for superoxide anion radical ( • O 2 − ) scavenging suggest that they likely mediate ROS scavenging, a conventional antioxidant mechanism, to inhibit ferroptosis. This proposal is further supported by the following three facts: (1) Ferroptosis is closely associated with extensive ROS (including LPO) production [ 21 , 27 , 28 , 29 ]; (2) the relative ferroptosis-inhibitory levels correlate with the relative antioxidant levels of piceatannol and astringin ( Table 1 and Figure 2 ); however, the antioxidant difference between the two stilbenes can be attributed to 3-OH glycosylation, according to a previous antioxidant structure–activity relationship analysis [ 30 , 31 ]; and (3) nowadays, many natural phenolic antioxidants have already been proven to be ferroptosis inhibitors, such as corilagin [ 6 ], baicalein [ 32 ], and isorhapontigenin [ 33 ].…”
Section: Resultsmentioning
confidence: 90%
“…Nevertheless, tannic acid can also be metabolized by human cells. Tannic acid and similar tannins such as strictinin [66] and pomegranate‐derived ellagitannin [67] successfully protect the cells from ferroptosis. These results suggest that tannic acid with a large size can pass through the cell membrane and be absorbed, and is therefore regarded as an effective and bioavailable ferroptosis inhibitor.…”
Section: Resultsmentioning
confidence: 99%